Investigation of atherosclerotic disease in renal transplanted recipients and on waiting list in ambulatory monitoring through carotid artery ultrasound - Campagnolo, Ângela Quatrin (2013)
Renal transplantation is the treatment of choice for patients with end-stage renal disease. The death proportion related to cardiovascular disease is currently increasing in those patients. Purposes: Assess carotid atherosclerosis prevalence in renal transplanted patients and on the waiting list for the procedure at the Santa Maria University Hospital by carotid arteries ultrasound and determining its correlation to the Framingham score. Methods: Cross-sectional prospective study assessed 59 renal transplanted and non-transplanted patients on the waiting list for renal transplant at the Renal Transplant ambulatory of the Santa Maria Hospital Universitário between January, 2012 and March, 2013. Carotid ultrasound was performed for diagnosis and quantification of carotid artery atherosclerosis, and to calculate the Framingham score. Results: Prevalence of carotid plaques was 59.38% in patients who underwent renal transplantation, and 70.37% from those on the waiting list. No significant association was found between groups related to the presence of carotid plaques (p = 0.379) or severity (p = 0.704). The group who underwent renal transplantation has been for longest time on dialysis (55.25 ± 44.16 months vs 28.15 ± 36.50 months, p = 0.00079), and presented lower mean age (45.09 ± 13.04 vs. 52.48 ± 14.18 years, p = 0.042), fewer diabetic patients (9% vs. 52%, p = 0.00033) and lower Framingham risk score (8.72% ± 7.5 vs. 16.51% ± 11.97, p = 0.002). There was no significant difference between presence of carotid plaque and time of renal transplantation (p = 0.399) or type of immunosuppressive regimen (p = 0.939). Intermediate correlation was found (Spearman coeff = 0.47, p = 0.0065) between the Framingham degree and the severity of carotid plaque in patients who underwent renal transplantation. Upon the logistic regression analysis for factors associated to the presence / absence of carotid plaque, an association was found between the Framingham score and the chance of carotid plaque (OR = 1.104 [1.008 to 1.210, CI OR 95%], p = 0.033). Conclusion: Carotid atherosclerotic disease has high prevalence in the population studied. Traditional cardiovascular risk factors used in the Framingham score have an important role in the development of carotid plaques.